(untitled) (American Journal of Human Psychology, 2023)
The Robbers Cave Experiment in the mid-1950s by Muzafer Sherif and his colleagues advanced the realistic conflict theory, whose main premise is that conflict is inevitable whenever two (or more) in-groups are brought together in mutual competition for scarce resources. This conflict is driven by prejudice and discrimination, and may take on various forms of hostilities and aggressions towards a competing out-group. However, a resolution of the conflict is possible when the two (or more) competing in-groups are forced to work together to attain mutually beneficial superordinate goals. Whereas the Robbers Cave Experiment suffers from serious questions of ethics and confirmation bias, the lessons that draw from the tested hypotheses have remained germane to the understanding of realistic conflict theory. In this study, the author seeks to reflect on this (in)famous experiment and draw poignant comparisons and lessons as they relate to some contemporary examples in political conflicts, racism, xenophobia, business workplaces, and mergers and acquisitions. The author repeatedly acknowledges the blurring influence of the criticisms of the experiment on the clarity of these reflections.